Clearance of obstructions of high passenger platforms - Yu. M. Lazarenko; V. V. Semerkhanov; D. I. Smirnov; I. V. Smelyanskiy (Вестник Научно-исследовательского института железнодорожного транспорта)
The article examines the issues of justification of the norms of clearance of obstructions of high passenger platforms of the railways 1520 mm wide. The authors conducted analysis of the valid regulatory documents establishing the clearance requirements to passenger platforms and developed the double-criteria method of assessment of the relevance of these requirements. Examinations were conducted by the scientists of JSC “VNIIZhT” together with the experts of Moscow directorate of infrastructure in order to make correct selection of the clearance of obstructions when constructing new high passenger platforms. Experts of JSC “VNIIZhT” developed explanation of the relevance of the clearance norms stated in GOST 9238–2013 and in the Standard code in the Russian Federation approved by the order of the Ministry of Transportation dated 21.12.2010 no. 286, as well as performed inspection of compliance of high passenger platforms recently constructed or being constructed now with the requirements of these regulatory documents.Analysis of actual clearance to obstructions of the used platforms by means of the double-criteria method of justification of the clearance of high passenger platforms allowed assessing compliance of the actual clearance to obstructions of the platforms with the passenger comfort requirements, as well as with GOST 9238–2013. Examinations confirmed that actual clearance to obstructions with regard to the tolerances in general comply with the standard. Requirements of GOST 9238–2013, which shall be followed for selection of the clearance to obstructions of high passenger platforms, are the primary requirements of the valid regulatory documents specifying the norms of the platform clearance to obstructions.